Effects of therapeutic exercise on disease severity, balance, and functional Independence among individuals with cerebellar ataxia: A systematic review with meta-analysis - Winser, Stanley; Chan, Ho Kwan; Chen, Wing Ki; Hau, Chung Yau; Leung, Siu Hang; Leung, Yee Hang; Bello, Umar Muhammad (Physiotherapy theory and practice, 2023)
Balance impairments are common in cerebellar ataxia. Exercises are beneficial in this population. Explore the benefits of therapeutic exercises on disease severity, balance and functional independence in cerebellar ataxia. Databases were searched from inception until July 2021. Methodological quality was assessed using the Physiotherapy Evidence Database (PEDro) scale and the Newcastle-Ottawa Scale (NOS); and quality of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tool. Twenty-six studies were included and eight studies of low to high PEDro methodological quality were meta-analyzed. 'Low' to 'moderate' GRADE quality evidence supports the use of therapeutic exercises to reduce disease severity, assessed using the Scale for the Assessment and Rating of Ataxia [weighted mean difference (WMD): −3.3; 95% confidence interval (95%CI): −3.7, −2.8; p < .01]; and improve balance, assessed using the Berg Balance Scale (WMD: 2.6; 95%CI: 1.1, 4.2; p < .01). The effect of therapeutic exercises on functional independence was insignificant (WMD: 1.6; 95%CI: −1.5, 4.6; p = .31). Low to moderate evidence from studies of low to high methodological quality provides some support for therapeutic exercises for reducing disease severity among non-hereditary degenerative cerebellar ataxia and improving balance among acquired cerebellar ataxia. Exercises did not benefit functional independence. Additional studies of large sample size and high methodological quality are necessary to substantiate these findings.